2012
DOI: 10.1002/ar.22479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triptolide on T‐Cell Receptor Beta Variable Gene mRNA Expression in Rats With Collagen‐Induced Arthritis

Abstract: Triptolide (TP) has been used in the treatment of rheumatoid arthritis (RA), but its mechanism of action is not understood. T-cell activation and associated release of cytokines appear to be major factors in the pathogenesis of RA. The overexpression of T-cell receptor (TCR) variable gene (V gene) fragments can cause the activation and infiltration of autoreactive T cells. This study examines the effects of TP on rats with collagen-induced arthritis (CIA). The levels of interleukin-10 (IL-10) in the serum were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…However, the clinical use of these therapies has been limited because of their adverse effects with a high frequency and high cost of treatment. Extracts of the herb Tripterygium Wilfordii Hook f. (TWHF), also known as “Lei Gong Teng”, are clinically used as one of the most common systemic treatments for (auto) immune disorders including RA, immune complex nephritis, and systemic lupus erythematosus [11, 12]. It has been extensively used for centuries in China because of its favorable cost-benefit ratio.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical use of these therapies has been limited because of their adverse effects with a high frequency and high cost of treatment. Extracts of the herb Tripterygium Wilfordii Hook f. (TWHF), also known as “Lei Gong Teng”, are clinically used as one of the most common systemic treatments for (auto) immune disorders including RA, immune complex nephritis, and systemic lupus erythematosus [11, 12]. It has been extensively used for centuries in China because of its favorable cost-benefit ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Although these drugs are all clinically used to relieve the severity of RA, slow this disease progression, and prevent the subsequent joint damage [8][9], their clinical use has been limited because of their adverse effects with a high frequency and high cost of treatment. Extracts of the Chinese herb Tripterygium Wilfordii Hook f. (TWHF), also known as “Lei Gong Teng”, are clinically used as one of the most common systemic treatments for (auto) immune disorders including RA, immune complex nephritis and systemic lupus erythematosus [10][11]. It has been extensively used for centuries in China because of its favorable cost-benefit ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The current researches on the mechanism of TPL in the treatment of RA mainly includes the following aspects: Wang et al () applied TPL to collagen‐induced RA mice, suggesting that TPL could improve arthritis symptoms of RA by inhibiting the secretion of inflammatory cytokines by T lymphocytes; Kong et al () proposed that TPL could inhibit the inflammation of RA by blocking the angiogenesis at the inflammatory site; Su, Sun, Ao, and Zhao () proposed that TPL could mediate the apoptosis of fibroblast‐like synoviocytes and inhibit their inflammation to improve the symptoms of RA. Fan et al () found that TPL could inhibit the degree of inflammation through TREM‐1 signaling pathway; Liu et al () proposed that TPL could block RANKL/RANK/OPG signaling pathways in collagen‐induced RA mice to prevent the formation of OCs from OCPs, thereby inhibiting bone destruction of RA.…”
Section: Discussionmentioning
confidence: 99%